Acute hand injuries in athletes - Rosenbaum, Y. A.; Awan, H. M. (The Physician and Sportsmedicine, 2017)
Hand and wrist injuries in athletes are common, representing between 3 and 25% of all sports injuries. As many as a quarter of all sports injuries involve the hand or wrist. We review the recent literature regarding acute hand injuries in athletes based on the structures involved - bone, muscle/tendon, ligament, and neurovascular - including diagnosis and pathophysiology of these injuries, focusing on athlete-specific facets of treatment, and when available, opinions on return to play.